Eight-year follow-up of central giant cell lesion treated with corticosteroid: Case report - Costa, Tila Fortuna; Dantas, Juliana Borges de Lima; Silva, Daniel Santana; Reis, Silvia Regina de Almeida; Marchionni, Antônio Márcio Teixeira; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2017)
Introduction: Central giant-cell granulomas (CGCL) are benign, but occasionally ag- gressive, lesions that traditionally have been treated surgically. Nonsurgical treatments, such as intralesional corticosteroid injections, systemic calcitonin and interferon have been reported. The advantages of this therapy include its less-invasive nature, the pro- bable lower cost to the patient and the preservation of important structures. Objectives: This paper aims to report a case of a pediatric patient with CGCL of the jaw, which was successfully treated with intralesional corticosteroid injections as it’s only therapy and discuss if there is an ideal waiting period between nonoperative treatment and the need for surgical intervention. Methods and Materials: an eight-year-old boy with a central giant cell lesion on the right side of the mandible was treated with intralesional corticos- teroids injections. Results and Conclusion: After an eight-year follow-up, the patient’s bony architecture was near normal. The panoramic radiography showed areas of new bone formation and neither recurrence nor side effects of the medication have been also detected. Is there an ideal waiting period between nonoperative treatment and the need for surgical intervention? It is estimated that a monitoring period of 6-8 years is necessary to determine the success of such treatment.